Determinant of corporate social responsibility in Islamic banking based on the Islamic social reporting index - Fanana Firdaus Salsabilah; Resfa Fitri (Journal of Islamic Accounting and Finance Research, 2023)
Purpose - This study aims to determine the level of CSR comparison in sharia-compliant banking based on the Islamic Social Reporting Index indicators and analyze the factors influencing its disclosure.Method - This study is quantitative research using secondary data. Population of this study is 9 Islamic Banks in Indonesia in 2017-2021. The selection of samples in this study used purposive sampling. The data were analyzed using Panel Data regression analysis, Classic Assumption test, F-test, and T-test.Result - The results showed that two of the four variables thought to have an impact on ISR disclosure are found to have a significant impact. In contrast to leverage, which has a negative but considerable impact on ISR disclosure, company age has a positive and significant impact. The other two factors (profitability and company size) had less of an impact on ISR disclosure.Implication - Islamic Commercial Banks in Indonesia suggest to improve the financial performance in Corporate Social Responsibility with Isamic Social Reporting Index.Originality - This is a study to prove the effect of corporate social responsibility disclosure on the annual report of Islamic banks using the Islamic Social Reporting Index indicator.